THE EFFECT OF SELF AFFIRMATION ON STRESS ON WOMEN IN WAITING FOR PREGNANCY - SHANTI NATALIA; Febriyanti Elmaristo Siki; Miftakhur Rohmah; Julia Siekmans (Journal for Quality in Women's Health, 2022)
Background : Stress infertility is a problem that is often faced by women of childbearing age. This of course will trigger stress to peak when the unexpected menstruation finally arrives, which in fact indicates that the wife is not pregnant. Methods: The research design is a one-group pre-post test design. Respondents were taken by purposive sampling technique with a sample of 30 people who met the inclusion and exclusion criteria. The independent variable is Self Affirmation and the dependent variable is Stress on Women in Waiting for Pregnancy Online Forum. The results of statistical tests using the Wilcoxon test. Results: The results showed that before self-affirmation, almost all respondents were as many as 15 (75%) in the category of severe stress while after self-affirmation almost all respondents as many as 17 (85%) in the category of mild stress.